1988
DOI: 10.1523/jneurosci.08-12-04628.1988
|View full text |Cite
|
Sign up to set email alerts
|

Timing factors in the coordination of speech movements

Abstract: Speech movement coordination involves substantial timing adjustments among multiple degrees of muscles and movement freedom. The present investigation examined the kinematic and muscle timing adjustments associated with the production of select speech movements. For oral closing movements, the timing of the upper lip, lower lip, and jaw peak velocities were found to be tightly coupled, apparently reflecting a coordinative strategy. In contrast, oral opening movements demonstrated reduced temporal coupling and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
66
1
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 43 publications
10
66
1
2
Order By: Relevance
“…Differences in inter-articulatory coordination and timing between opening and closing gestures were reported by Gracco (1988) (2000) who investigated speech acquisition and explained it in terms of the preferred co-occurrences between certain consonant and vowel places of articulations in human languages. According to MacNeilage and Davis, bilabials would be simpler to produce than coronals, since the first require only a cyclical jaw motion as in babbling and mastication, whereas the latter need an active motion of the tongue which is independent of jaw motion.…”
Section: Interarticulatory Coordination In Speechmentioning
confidence: 91%
“…Differences in inter-articulatory coordination and timing between opening and closing gestures were reported by Gracco (1988) (2000) who investigated speech acquisition and explained it in terms of the preferred co-occurrences between certain consonant and vowel places of articulations in human languages. According to MacNeilage and Davis, bilabials would be simpler to produce than coronals, since the first require only a cyclical jaw motion as in babbling and mastication, whereas the latter need an active motion of the tongue which is independent of jaw motion.…”
Section: Interarticulatory Coordination In Speechmentioning
confidence: 91%
“…In this re-j spect, it is important to notice the between-subject variabil-1 ity in the interlip interval data for both groups (see Figure 5). I However, Gracco (1988) also indicated that at the same time I the individual muscle onsets are adjusted in a consistent I manner. This was taken as evidence that synergistic mus-| cles are initiated by a common control signal, reflecting a 1 functional relationship between individual articulators as I part of a coordinative structure (see also Gracco, 1994;I Saltzman & Munhall, 1989), In the present study, it was ; shown that across subjects (Table 3) there were co-varia tions in the onset of IEMG of synergistic articulators (upper lip and lower lip).…”
Section: Relative Timing Datamentioning
confidence: 99%
“…For example, for the bilabial closure a very consistent advancement of the upper lip velocity peak for the closing movement relative to the lower lip and jaw velocity peaks has been found ͑see, e.g., Gracco and Abbs, 1986;Gracco, 1988;van Lieshout, 1995;Kollia et al, 1995͒. The stability of such relatively time-locked interarticulator cohesion has been experimentally tested by varying external parameters such as speech rate and stress placement.…”
Section: Introductionmentioning
confidence: 97%
“…In former studies the strength of cohesion has been found to vary with several aspects, e.g., closing movements are more tightly coupled than opening movements ͑e.g., Gracco, 1988;Hertrich and Ackermann, 2000͒. Furthermore, articulators controlled by different tract variables such as the vocal folds and velum exhibit a smaller degree of interarticulator cohesion with the jaw than articulators controlled by a single tract variable such as upper lip and jaw ͑see, e.g., Gracco and Löfqvist, 1994;Kollia et al, 1995͒ as measured by a greater variability in timing parameters.…”
Section: Introductionmentioning
confidence: 99%